Are we straining to succeed? Prevalence of work-related musculoskeletal disorders among dentists in teaching hospitals - Muhammad Arslan Rana; Saad Shahnawaz Ahmed; Nimrah Awan; Nida Siddique (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the prevalence of work-related musculoskeletal disorders among dentists. Method: The cross-sectional study was conducted in Islamabad, Pakistan, from January to March 2023 after approval from the ethics review committee of the Islamic International Dental Hospital, Islamabad, and comprised dentists associated with 4 major dental teaching hospitals in the city. Data was collected using a self-administered questionnaire adapted from literature. Prevalence of work-related musculoskeletal disorders was explored along with its association with variables, like age, gender, experience, designation and history of injury. Data was analysed using SPSS 26. Results: Of the 250 forms distributed, 188(75.2%) were received back duly filled. Among the respondents, 34% were males and 66% were females, and the overall prevalence of work-related musculoskeletal disorders was 91.5%. There was no significant difference among the variables based on anatomic site-specific data, except the designation variable, with individuals having a history of injury to neck (p=0.027) or shoulder (p=0.001) and those designated as professor (p=0.040) were significantly at risk of developing pain due to work-related musculoskeletal disorders. Conclusions: A significantly high number of dentists were fund to have some form of work-related musculoskeletal disorder. Key Words: Work-related musculoskeletal disorder, Prevalence, Dentists, Neuropathy, Islamabad.